SERTIFIKASI DAN LISENSI TENAGA PERPUSTAKAAN SEKOLAH/ MADRASAH - Komaruddin, Yooke Tjuparmah S; Susilana, Rudi (Universitas Pendidikan Indonesia, 2012)
Abstrak Sertifikasi dan lisensi tenaga perpustakaan sekolah/ madrasah (TP-SM) merupakan dokumen yang menandakan pengakuan bahwa seseorang memiliki kewenangan untuk melaksanakan tugas sebagai tenaga pengelola perpustakaan di lembaga pendidikan (sekolah dan madrasah) secara profesional. Sertifikasi dan lisensi hanya diberikan kepada seseorang yang telah memenuhi persyaratan kualifikasi dan penguasaan tentang standar kompetensi tenaga perpustakaan sekolah sebagaimana yang telah ditetapkan dalam Permendiknas Nomor 25 Tahun 2008. Penguasaan tentang standar kompetensi tersebut merupakan dasar dan pedoman dalam penyelenggaraan pendidikan dan pelatihan tenaga perpustakaan dan pendidikan profesi pustakawan untuk menerbitkan sertifikasi kompetensi dan pemberian lisensi tenaga perpustakaan dan pustakawan. Proporsi yang sangat rendah tentang keberadaan pustakawan dan/atau tenaga pengelola perpustakaan tentulah menjadi pekerjaan rumah bagi semua pihak, baik bagi pemerintah (Direktorat terkait di Kemdiknas dan Kemenag), Perpusnas, perguruan tinggi pengelola program studi perpustakaan, dan asosiasi profesi. Hal ini terkait dengan kepemilikan perpustakaan dan tenaga pengelola perpustakaan di sekolah/ madrasah yang harus dapat terpenuhi selambat-lambatnya pada Juni 2013 atau 5 (lima) tahun setelah peraturan tentang hal tersebut ditetapkan.Permasalahannya adalah (1) Apakah semua tenaga perpustakaan sekolah yang ada saat ini sudah profesional?; (2) Kualifikasi dan kompetensi apa yang dibutuhkan agar mereka dapat menjadi profesional?; (3) Apa bukti yang menunjukkan bahwa mereka memiliki kewenangan sebagai tenaga perpustakaan yang profesional?; (4) Pendidikan atau pelatihan yang bagaimana yang dibutuhkan agar dapat mempersiapkan dan mengembangkan seseorang menjadi tenaga perpustakaan yang profesional? (5) Bagaimana kesiapan Perguruan Tinggi untuk mempersiapkan Tenaga Perpustakaan Sekolah/Madrasah ini? Jawabannya tentu perlu dikaji secara teoritik dan empirik. Sebagai bahan diskusi pertanyaan (1) dan (2) akan dijawab dengan paparan pada bagian B, pertanyaan (3) dan (4) akan dijawab melalui paparan pada bagian C, sedangkan pertanyaan ke (5) akan dijawab melalui paparan bagian D, dengan ilustrasi memaparkan Program Studi Perpustakaan dan Informasi, Jurusan Kurikulum dan Teknologi Pendidikan, Fakultas Ilmu Pendidikan, Universitas Pendidikan Indonesia. Sertifikasi dan lisensi tenaga perpustakaan akan menghasilkan tenaga yang profesional apabila melibatkan berbagai unsur sebagai berikut, yaitu: perguruan tinggi penyelenggara disiplin ilmu perpustakaan, lembaga yang mengelola perpustakaan (Perpusnas), lembaga yang mengelola tenaga perpustakaan (Kemdiknas) dan asosiasi profesi perpustakaan. Kata Kunci: Pustakawan, Tenaga Pengelola Perpustakaan, Sertifikasi, Lisensi, Perpustakaan Sekolah/Madrasah, Pendidikan Pustakawan Abstract Certification and license of school librarian/ Madrasah librarian (Tenaga Pustakawan-Sekolah/Madrasah - TPSM) refers to a document admitting that an individual has a right to execute a task assuming the responsibility to manage a library at an educational institution (school or Madrasah) professionally. The certification and the license are issued to individuals who have met some qualification as required so as to describe a mastery in a standardized competencies owned by school librarians as enacted by Permendiknas No.25/2008 (an Act of the Ministry of Education and Culture). The mastery of the aforementioned competencies serves as basics and principles in operationally running education and training for librarians and professional librarian education prior to the issuances of competency certification and license for assistant librarians and librarians. Less than adequate proportion of the existence of librarians remains a big task to be done by all parties including the Government (directorates, Kemendikbud (Ministry of Education and Culture), and Ministry of Religion), Perpusnas (National Library of Indonesia), universities running the programs of library schools, and profession associations. It brings with it some concerns with services libraries and their librarians have to provide. According to the Permendiknas, by June 2013 (five years after the issuance of the Act) schools and Madrasah have to equipped themselves with libraries managed by librarians. Problems arise once concerns on providing library services have to be working: (1) Are all school/Madrasah librarians on duty professional in category?, (2) What qualifications and competencies should the librarians have to be professional?, (3) What could be the proof that the librarians have every right to work as professionals?, (4) What kind of education and training do the librarians need to undergo to have a good command of managing library collections professionally?, (5) How prepared are higher education institutions in training librarians to have adequate competencies in managing libraries? Answers to the queries need to be explored both theoretically and empirically through a study. To initiate a discussion, questions (1) and (2) will be entertained through explanation in Part B; questions (3) and (4) will be entertained through explanation in Part C while questions (5) will be entertained through explanation in Part D with an illustration of Library and Information Studies-Department of Curriculum and Educational Technology-Faculty of Education-UPI (Universitas Pendidikan Indonesia-Indonesia University of Education). Certification and license for school librarians will work the excellent way to produce professionals in librarianship if the elements involved in the program are promising enough in terms of qualifications. Those to be involved include universities running the programs of library studies, institutions with the power of managing libraries nationwide including Perpusnas, institutions which concern in establishing libraries (Kemendikbud), and profession associations in librarianship.Key words: librarian, library managers, certification, license, school/Madrasah libraries, training for librarians.